Identity Politics and National Integration; A Case Study of the Sunni-Shia Conflict in Sampang, 2012 - Neneng Sobibatu Rohmah (International Journal of Interreligious and Intercultural Studies, 2021)
This research attempts to examine the identity politics conflicts that occur between Sunni-Shia in Sampang. This conflict was based on religious identity that is used as a force in exerting pressure on different groups. On the other hand, national integration is needed as a form of acknowledging and accommodating differences through policies issued. Integration must be a two-way adaptation process involving changes in values, norms and behaviors. This study aims is also to determine whether the Sunni-Shia conflict in Sampang which is motivated by identity politics has now reached the direction of national integration or not. David Miller's theory of identity politics and Chantal Lacroix's national integration was used in this study. The methodology used is qualitative specifically with a case study approach. The findings showed that the Sunni-Shia conflict in Sampang has been seen towards integration of Tajul Muluk attitude and his followers’ decision to leave their faith and return to the doctrines of the majority community, Sunni. This makes the absence of a two-way adaptation process appears by abandoning their beliefs and following the wishes of the majority. The role of the state in fighting for freedom of religion and belief in Indonesia was very weak even though the constitution in Indonesia guarantees freedom of religion is strong enough. Therefore, the application of their efforts should have some supervisions.